Bugs detection using acoustic location - Самосуд, Зоя Олегівна (Ukrainian Scientific Journal of Information Security, 2015)
This paper adduces the analysis of the efficiency of modern equipment and existing methods of bugs detection. The main characteristics, physical properties, classification features and bugs working principle, the characteristics of the information loss channels that they create was reviewed. It is well known that the research of the basic and most effective methods of bugs’ detection, conduct, based precisely on the principles of their work, physical characteristics and the methods of their installation. Considering that nowadays the most multipurpose device is a non-linear search radar, which may find any type of electronic devices of covert information collection in any of its condition, the main principle of its work was reviewed and main disadvantages was marked. Also the main advantages and disadvantages between existing hardware tools and complexes were marked out. Highlighted that large and expensive devices are used for bugs detecting, searching methods are require lots of time. Bug detection device based on the main principle of work to fix the distance to the object by the time of voice passing to this object was suggested. Suggested method contributes to conclude problems of mobility, cost and searching time reduction.